EFFECTIVENESS OF WORK MUTATION POLICY AND WORK PERFORMANCE IN IMPROVING PERFORMANCE IN BATAM CITY GOVERNMENT - Purwaningrum, Ajeng Handayani; Hansyah, Praida (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2025)
The purpose of the study was to determine the effectiveness of the Batam City Government in carrying out job transfers and work performance on employee performance and its implications. This research design is included in quantitative descriptive research, namely statistical analysis used to describe, summarize, and analyze quantitative data. The subject of this study was in the Batam City Government with a population of 5,541 people. So the sampling using the Slovin formula obtained a sample of 100 people with an error rate of 10% so that the sampling used simple random sampling. The data analysis tool used is path analysis multiple linear regression. The results of this study conclude that job transfers and work performance as independent variables have a significant effect both partially and simultaneously on the performance of Batam City Government employees. Job transfers to Batam City Government employees are carried out based on applicable procedures so that the existence of these procedures illustrates the effectiveness of the job transfer policy has met the applicable requirements.